Changes in severity of myocardial infarction and three year survival rates after myocardial infarction in Auckland, 1966-7 and 1981-2. Issue 6647 (20th August 1988) - Stewart, A. W.; Fraser, J.; Norris, R. M.; Beaglehole, R.
Abstract : Mortality from coronary heart disease has been declining steadily over the past 20 years in Auckland. The possibility that improved survival contributed to this decline was examined in patients who survived four weeks after myocardial infarction, changes in the severity of the disease being controlled for. Patients who had had myocardial infarction in 1966-7 (191 patients) or 1981-2 (203) were compared to determine whether three year survival rates had changed and the severity of the disease altered. With a coronary prognostic index taken as the measure of severity the 1981-2 group had significantly more severe myocardial infarctions than the 1966-7 group, but despite this the three year survival was significantly better (86% in the 1981-2 group v 75% in the 1966-7 group). These findings suggest that improved survival after myocardial infarction contributed to the decline in mortality.